PERSEPSI MAHASISWA TERHADAP IMPLEMENTASI UANG KULIAH TUNGGAL PADA JURUSAN MANAJEMEN PENDIDIKAN ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Suarga; Tsaqif, Ahmad Nahjul; Setiawan, Anugerah; Fajar, Farhan Nur; Aspirah (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
This research examines students' perceptions of the implementation of Single Tuition Fees (UKT) in the Islamic Education Management Department, Tarbiyah and Teacher Training Faculty, UIN Alauddin Makassar. Using qualitative descriptive methods, this research found that students had positive and negative views about UKT. Several informants criticized the determination of UKT groups as not being on target and the existence of additional payments outside of UKT, such as books. However, the majority of students gave a positive perception, considering that the implementation of UKT was in accordance with their current information and knowledge, although there were hopes for improvement in the future.